2021
DOI: 10.1158/0008-5472.can-20-2990
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Based Approaches for Cancer Immunotherapy

Abstract: Adoptive cell therapy with genetically modified T cells has generated exciting outcomes in hematologic malignancies, but its application to solid tumors has proven challenging. This gap has spurred the investigation of alternative immune cells as therapeutics. Macrophages are potent immune effector cells whose functional plasticity leads to antitumor as well as protumor function in different settings, and this plasticity has led to notable efforts to deplete or repolarize tumor-associated macrophages. Alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
301
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(342 citation statements)
references
References 119 publications
3
301
1
4
Order By: Relevance
“…Previous studies using experimental models have shown that depletion of macrophages can inhibit tumor progression and metastasis. On the other hand, it is also known that macrophages inherent anti-tumor potential through antigen presentation and secretion of anti-tumor factors, active T cells, and NK cells [ 9 , 88 ]. Hence, it is necessary to clarify their functions by determining the mechanisms of macrophage polarization and the functions of macrophages during tumor development and progression ( Figure 3 ).…”
Section: Tams Are Involved In Tumor Progressionmentioning
confidence: 99%
“…Previous studies using experimental models have shown that depletion of macrophages can inhibit tumor progression and metastasis. On the other hand, it is also known that macrophages inherent anti-tumor potential through antigen presentation and secretion of anti-tumor factors, active T cells, and NK cells [ 9 , 88 ]. Hence, it is necessary to clarify their functions by determining the mechanisms of macrophage polarization and the functions of macrophages during tumor development and progression ( Figure 3 ).…”
Section: Tams Are Involved In Tumor Progressionmentioning
confidence: 99%
“…Macrophages exhibit a high degree of plasticity when exposed to various environmental stimuli. They are polarized to one of two opposite types in vitro , classically activated M1 macrophages that can be induced by lipopolysaccharide (LPS), interferon-γ (IFN-γ), or colony-stimulating factor 2 (CSF2, also known as granulocyte-macrophage colony-stimulating factor) or alternatively activated M2 macrophages that can be induced by interleukin 4 (IL4), IL13, or CSF1 (also known as macrophage colony-stimulating factor) ( 1 3 ). M2 macrophages are further categorized as M2a, M2b, M2c, and M2d cells upon stimulation of different M2 drivers ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…M2 macrophages are further categorized as M2a, M2b, M2c, and M2d cells upon stimulation of different M2 drivers ( 4 ). Generally, M1 macrophages exert an immune protective role via the secretion of pro-inflammatory cytokines, whereas M2 macrophages are characterized by anti-inflammatory properties, which contribute to tissue remodeling and tumor progression ( 3 ). Multiple co-stimulatory and antigen-presenting molecules are expressed on the cell membrane of antigen-presenting cells (APCs), including macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…With this strategy, developed by Klichinsky et al. in 2016 ( 100 ), CAR-modified macrophages eliminated tumor cells more effectively than non-CAR-modified M1-like macrophages in vitro and in vivo ( 101 ). The creators of this technology have developed the company CARISMA therapeutics which has an ongoing phase I clinical trial on CAR-M for treating HER2- overexpressing solid tumors (including squamous carcinoma) (NCT04660929).…”
Section: Macrophages As Drug Delivery Vehiclesmentioning
confidence: 99%